Determinants of Company Value: Corporate Social Responsibility and Financial Performance - Octalia, Milcha Aurellia; Retnani, Endang Dwi (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2024)
This research aimed to examine the effect of CSR (Corporate Social Responsibility), and financial performance on firm value (PBV) at mining companies 2016-2021. We collected data by using purposive sampling technique. There were 19 samples from 62 mining companies. Furthermore, in total, there were 114 data samples. The result concluded that ROI had a positive impact on corporate value. It meant the higher the ROI was, the higher the firm value would be. Consequently, it would give a positive signal to the investors. However, DER had a negative effect on PBV. This meant, how high or low the companies' DER was, the lower the firm value would be, as there were additional costs. In addition, both CSR and ROE did not affect firm value. In brief, the higher the firm value would be affected by other factors outside the research variables Keywords: corporate social responsibility, return on equity, return on investment, financial performance, firm value.